2019
DOI: 10.1038/s41430-019-0453-6
|View full text |Cite
|
Sign up to set email alerts
|

Intake of milk and other dairy products and the risk of bladder cancer: a pooled analysis of 13 cohort studies

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…In addition, evidence suggests that factors related to lifestyle, physical activity and diet, might also affect the risk of BC 4,5 . Previous research on diet and BC reported that higher intakes of fluid, fruit, vegetables and yoghurt are associated with a reduced risk of BC 6 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, evidence suggests that factors related to lifestyle, physical activity and diet, might also affect the risk of BC 4,5 . Previous research on diet and BC reported that higher intakes of fluid, fruit, vegetables and yoghurt are associated with a reduced risk of BC 6 …”
Section: Introductionmentioning
confidence: 99%
“…Another meta-analysis by Bermejo et al ( 11 ) also indicated a reduced risk of bladder cancer associated with medium consumption of total dairy products and with medium and high consumption of milk and fermented dairy products. However, a pooled analysis of 13 cohort studies by Acham et al ( 12 ) failed to find a significant association between total or individual dairy products and bladder cancer risk. This study aims at contributing to this debate by considering the association between dairy product consumption and bladder cancer risk in the prostate, lung, colorectal, and ovarian (PLCO) cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Previous epidemiological research on diet and BC reported that high amount of fluid, fruit, vegetable, yogurt, whole grain and dietary fiber intake were associated with a reduced risk of BC [9][10][11], while higher intake of barbecued meat, pork, and total fat may increase BC risk [8]. At last, organ meat consumption has also been associated with BC development [12].…”
Section: Introductionmentioning
confidence: 99%